Alternasi dalam fonologi subdialek Kedah Utara (Jurnal Bahasa, 2009)
The purpose of this study is to reveal the phonological processes of North Kedah sub dialect as well as to illustrate the distributions of its phonemes. Data of this study were gathered from the dialect spoken by native speakers of North Kedah sub dialect who live in Naka, Pedu, and Kuala Nerang areas (in the district of Padang Terap, Kedah). It is important to note here that previous studies (literature review) tne dot equalize the phonological process of North Kedah sub dialect with the Coastal Kedah sub dialect (i.e. Kedah standard language). The present study notwithstanding, found that the North Kedah sub dialect do have differences of phonological process, such as consonant reduplication as substitutes to the nasal assimilation process (homorganic nasal-obstruen), coalescent assimilation of segments and aspiration elements. This study shows that the existence of consonant reduplication (in the word medial position of the present data) is the result of particular phonological processes (as in assimilation and syllable restructuring) which is deemed to concur with specific phonological rules and contexts. The researcher is of opinion that this study has, at least, revealed that North Kedah sub dialect do have special characteristics that require special consideration. The particular characteristics as indicated throughout this study may differentiate North Kedah sub dialect fom other variation of Kedah dialect (i.e. the Coastal Kedah sub dialect).